EXTRACT OF Caulerpa lentilliera EXTRACTED WITH SOLVENTS OF DIFFERENT POLARITY - Annisa Alif; Edison Edison; Andarini Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to determine the yield of Caulerpa lentillifera extracted with polar (methanol p.a.), semi-polar (ethyl acetate p.a.) and non-polar (n-hexane p.a.) solutions. The research method was explorative, the data is analyzed descriptively. The analysis parameter was yield. The results showed that Caulerpa lentillifera extracted with different solvent solutions had successively methanol, ethyl acetate, and n-hexane yields of 0.70%, 0.58%, 0.53%. The highest yield value was produced by methanol extract (polar) of 0.70%. Keywords: Caulerpa lentillifera dried, extract, identification, yield.